REVEALING CHARACTERS’ SOCIAL IDENTITY THROUGH REFERRING EXPRESSIONS IN “ETERNALS: : THE 500 YEAR WAR” COMIC - Amin, Mohammad Syauqil (Language Horizon: Journal of Language Studies, 2025)
Despite being fictional works, comics share similarities with reality, where the characters often use different expressions in different contexts. This study examined the social identity shown by the referring expressions the characters used to refer to the enemy, as well as the way they negotiate their social identity among others. By using the documentation method, this study collects its data from the Eternals: The 500 Year War comic. A qualitative method is used to analyze this study, following the data gathered in this study. The result shows that the characters in this comic used all forms of referring expression, including proper nouns, definite and indefinite noun phrases, and pronouns, where the most common forms used are the definite and indefinite noun phrases. The result also shows that the characters show similarity by using more specific expressions, while more generic expressions are used to show differences between the speakers and listeners. The researcher also found that the characters in this comic used three types of maxims to negotiate their identity among others, which are the unmarked-choice maxims, the exploratory-choice maxims, and the multiple identity maxims. The most common maxim used by the characters is the exploratory-choice maxim, since the characters mostly just met one another.